Mercado de trabalho em Sergipe : características da informalidade entre 2012 e 2019 - Matos Junior, Claudimir dos Santos (2022)
Social transformations in all their dimensions also affect the labor market, which has been marked by the direction of a significant portion of the economically active population to the performance of labor activities characterized as informal. The study analyzes what are the characteristics of informality in the labor market of Sergipe between the years 2012 and 2019. Thus, it aims to analyze the informality of the labor market in Sergipe, based on the variables gender, education level, income, position in occupation and grouping of economic activities, through data from PNAD Continuous in the period 2012 to 2019. The temporal cutout comprises the years 2012, 2015, 2017, and 2019, in order to allow a comparison of the results in the long term, as well as the research carried out does not deal with the Covid-19 Pandemic period, i.e., the analyses carried out refer to the pre-pandemic period. The spatial cutout worked on in the text includes the state of Sergipe, because the rates of unemployment and informality are relevant for the construction of the research, according to data from the IBGE. As for the methodology, the research can be considered qualitative, descriptive, exploratory, using descriptive statistics as a method of data analysis. This is a bibliographical research made possible by a review of literature in the area of authors who work on the theme, and a documentary research. The analysis of the real income shows that the average income of the sergipan worker with a signed portfolio, positioned itself in a downward movement in the year 2019. This confirms the weakened position of women in the labor market, either by their insertion in informality or by the perception of lower wages even when they have high levels of education. The main contribution of the study is shown in the creation of a panorama that reveals important socioeconomic conditions for the creation of public policies, once the results reinforce the need to address the theme, presenting informality as deleterious in the economy of Sergipe, directly impacting society and the performance of public agents. Thus, from the studies carried out, it was possible to present a technical report where a recommendation of actions to improve the informality panorama is presented.